2022
DOI: 10.1007/s12350-020-02457-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of FDG PET/CT imaging in patients with surgically managed infective endocarditis: results of a retrospective analysis at a tertiary center

Abstract: Background We assessed the diagnostic value of FDG PET/CT in a real-world cohort of patients with surgically managed infective endocarditis (IE). Methods We performed a retrospective analysis of all patients hospitalized in a tertiary IE referral medical center from January 2014 to October 2018 fulfilling the following criteria: ICD-10 code for IE and OPS code for both, heart surgery and FDG PET/CT. Results Final an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…More recent trials show higher sensitivity and specificity than older ones. It has comparable performance in both biological and mechanical prosthetic valves [ 15 , 17 , 59 , 60 , 61 , 62 , 63 ]. It is especially useful when prosthetic valve-related artefacts impair assessment via TTE and TEE [ 64 , 65 ].…”
Section: Nuclear Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent trials show higher sensitivity and specificity than older ones. It has comparable performance in both biological and mechanical prosthetic valves [ 15 , 17 , 59 , 60 , 61 , 62 , 63 ]. It is especially useful when prosthetic valve-related artefacts impair assessment via TTE and TEE [ 64 , 65 ].…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…It is especially useful when prosthetic valve-related artefacts impair assessment via TTE and TEE [ 64 , 65 ]. It is also useful in the setting of culture-negative IE with fastidious organisms [ 44 , 57 , 59 , 60 , 61 , 62 , 63 ]. From a prognostic standpoint, positive FDG valvular uptake is associated with worse outcomes (death, hospitalizations, IE recurrence, acute heart failure, new embolic event) [ 66 ].…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…However, another study showed that the improved sensitivity afforded by the addition of 18 F-FDG PET to modified Duke's criteria when compared against surgical diagnosis was only apparent for patients with prosthetic valve disease. 48 Hence, the absence of 18 F-FDG uptake in native valve endocarditis cannot reliably exclude infection. Several hypothetical explanations for the higher number of false-negative scans in native valve endocarditis compared to prosthetic valve endocarditis have been proposed, including potentially smaller vegetations that lack involvement of paravalvular structures, better response to initial antibiotic treatment, and differences in neutrophil content and fibrosis resulting in less inflammation.…”
Section: Diagnostic Accuracy Of Pet Imaging For Native Valve Infectionsmentioning
confidence: 99%
“…These valves regularly deflect the echo beam leading to reduced sensitivity of echocardiography for the detection of IE. F-18-FDG PET/CT is known to have a high sensitivity and specificity, which may vary within patient characteristics and is especially useful in patients whose prosthetic valves had been implanted >3 months ago [7,12,32,33].…”
Section: Patient Population and Affected Valvesmentioning
confidence: 99%
“…These have an overall sensitivity of 80-90%, which is significantly lower in specific cases [10,11]. Especially in patients with prosthetic valves, the use of 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (F-18-FDG-PET/CT) may be helpful [12]. The valve vegetation is the nidus of IE and consequently serves as the main target for preoperative imaging and intraoperative diagnosis.…”
Section: Introductionmentioning
confidence: 99%